Relative ergodic properties of C*-dynamical systems - Duvenhage, Rocco; Mukhamedov, Farrukh (World Scientific Publishing, 2014)
We study various ergodic properties of C*-dynamical systems inspired by unique ergodicity. In particular we work in a framework allowing for ergodic properties defined relative to various subspaces, and in terms of weighted means. Our main results are characterizations of such relative ergodic properties, ergodic theorems resulting from these properties, and examples exhibiting these properties.